(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article explores key trends in the evolution of the international tourism terminological system within the context of the emerging global tourism landscape. The author emphasizes that the tourism terminological system mirrors the complex and multifaceted nature of the tourism industry and plays a crucial role in shaping tourist culture by articulating tourism concepts of both universal and national significance. The discussion centers on the main approaches to interpreting terms and concepts in tourism. The article demonstrates that the international tourism terminological system is a distinctive linguocultural cognitive phenomenon. It also highlights the system’s role in structuring the conceptual framework of a multicultural and multilingual tourism worldview.